National conference on Spain : save Spain, save Britain, save peace (leaflet)
018b-0052-001 NATIONAL CONFERENCE ON SPAIN SAVE SPAIN, SAVE BRITAIN, SAVE PEACE 125 New Bond Street, London, W.1. Telephone: MAYfair 8787 April 6, 1938. The news from Spain has prompted us to write to you. We ask you to join in a great and urgent effort to arouse public opinion in support of the Spanish people who have fought so long and courageously. Must all their hopes and sacrifices for a better, freer Spain be now silenced by the overwhelming weight of recent German and Italian intervention? People of all political opinions in this country are at last coming to realise the desperate danger not to Spain alone, but to ourselves, the Empire, the French, and all the remaining free peoples, if Spain goes the way of Austria. The insurgents could not win if the Spanish Government had the freedom for which it has long asked, to buy the aeroplanes, anti-aircraft guns, artillery, and tanks to arm its man-power and defend its civilian population. The Spanish Government asks for no "Intervention" other than to be given this freedom. Everyone can do something. Will you help? 1. Write immediately to your Member of Parliament, telling him what you feel. Or better still, go and see him at the House of Commons. 2. Write to the Press, both local and national. 3. Join in any and every local meeting and demonstration of protest organised by your Peace Organisation, League of Nations Union, Council of Action, Trades Council, political party, Spanish Aid Committee, or whatever it may be. 4. Get in touch with such bodies and offer your help. 5. Get your friends and neighbours together. Organise large or small meetings yourself. Ask your M.P. to come and explain his position, and either to help you or to justify his attitude. 6. Approach any organisation you may be connected with and collect signatures among your friends urging the Mayor to call a Town's Meeting on this subject. 7. Get your organisation to support the National Conference which is to be held on April 23rd in the Queen's Hall, London. Let it be the culmination of a nation-wide campaign. 8. Offer to help by distributing the leaflets which can be obtained from the Conference Secretary at the above address. 9. Send us donations to cover the cost of this. 10. Think for yourself of any and of every other way that you can rouse public opinion. It need not be too late to SAVE SPAIN AND SAVE PEACE Initiated by the following ten M.P.'s :— Richard Acland, Katharine Atholl, David Grenfell, Megan Lloyd George, Geoffrey Mander, Harold Nicolson, Philip Noel-Baker, Eleanor Rathbone, Wilfrid Roberts, Ellen Wilkinson. Supported by :— Vernon Bartlett, the Rev. A.D. Belden, Professor J.D. Bernal, Lady Violet Bonham-Carter, Professor E. Carritt, Sir Peter Chalmers Mitchell, Air-Commodore L.E.O. Charlton, Seymour Cocks, M.P., Sir Stafford Cripps, M.P., the Bishop of Chelmsford, the Dean of Chichester, G.D.H. Cole, Mrs. Corbett Ashby, Professor F.M. Cornford, A.J. Cummings, the Rev. Canon L. Donaldson, V. Duncan Jones, Sydney R. Elliott, Lord Faringdon, Gwen Ffrangcon Davies, Commander R. Fletcher, M.P., Isabel Fry, Margery Fry, Victor Gollancz, James Griffiths, M.P., Professor J.B.S. Haldane, Lady Hall, G.H. Hall, M.P., J.F. Horrabin, Kenneth Ingram, John Jagger, M.P., C.E.M. Joad, Lady Jowitt, Professor Harold Laski, Will Lawther, Lady Layton, Professor H. Levy, the Earl of Listowel, J.C. Little, Lady Marley, Lord Marley, Lord Meston, Major J. Milner, M.P., Naomi Mitchison, Professor Gilbert Murray, H.W. Nevinson, Sean O'Casey, D.N. Pritt, M.P., Viscountess Rhondda, J. Robertson Scott, Evelyn Sharp, Sir Archibald Sinclair, M.P., F. Smith, Hannen Swaffer, J.E. Swan, M.P., Professor R.H. Tawney, Sir Charles Trevelyan, A.M. Wall, Rebecca West, W. Whiteley, M.P., Tom Williams, M.P., Ted Willis. 292/946/18b/52